ANTIBIOTIC SENSITIVITY OF STAPHYLOCOCCUS AUREUS STRAINS ISOLATED FROM FISHERY PRODUCTS - SANJEEV, S; IYER, K MAHADEVA; RAO, C. C PANDURANGA (Fishery Technology, 2017)
During the course of an investigation on the incidence of Staphylococcus aureus contamination in frozen crab meat, frozen prawns and dried fishes from Cochin, 116 strains of S. aureus were isolated. The sensitivity of the isolated strains towards nine antibiotics showed that all the S. aureus strains were sensitive to kanamycin and streptomycin (100%). Sensitivity to other antibiotics like chloramphenicol, polymyxin-B, erythromycin, tetracycline, neomycin, penicillin and ampicillin were shown by 98.28, 93.10, 87.93, 68.10, 67.24, 56.90 and 55.17 percent of the isolates respectively.